A review on writing metacognitive awareness of Turkish advanced level EFL learners - Özkan Kırmızı; İrfan Tosuncuoğlu (Informascope, 2019)
The present study was undertaken to measure the metacognitive writing awareness of university-level learners. The participants of the study are 101 students of English Language and Literature, enrolled at a state university in Turkey. The grade level of the students ranges from the first grade to the fourth grade. In order to collect data, a questionnaire, developed by Farahian (2017), was used. This questionnaire measures the awareness of metacognitive writing with regard to knowledge of cognition and knowledge of regulation. Knowledge of cognition is studied under the following sub-scales: (a) declarative knowledge (person), (b) declarative knowledge (task), and (c) procedural knowledge. Knowledge of regulation was studied in terms of (a) planning and drafting, (b) general online strategies (c) monitoring and revision. Descriptive statistics were used to analyse the data obtained and tentative results showed that students have a moderate level of writing awareness.